Comparison of Pethidine and Dexmedetomidine for the Control of Intraoperative Shivering Under Spinal Anesthesia - Viral Prakashkumar Patel; Shital Hardik Halvadia (Academia Anesthesiologica International, 2020)
Background: Spinal anesthesia significantly impairs the thermoregulation system by inhibiting tonic vasoconstriction, which plays a significant role in temperature regulation. Various non-pharmacological and pharmacological methods are available for the control of shivering during anesthesia. The present study was done with an aim to compare the two drugs Pethidine and Dexmedetomidine for the control of intraoperative shivering under spinal anesthesia.Subjects and Methods:A prospective randomized study was carried out in the Department of Anaesthesiology, on 100 patients who developed intra-operative shivering following spinal anesthesia for numerous surgical procedures. When patients developed shivering of higher than mentioned grades, they were randomly assigned to one of the 2 study groups: Group D- Dexmedetomidine group receiving single intravenous bolus dose of 0.5mcg/kg over 5 min.  Group P: Pethidine group patients receiving 0.5mg/kg Pethidine IV over 5 min. Patients were intently monitored for the failure of the drug, Recurrence of shivering and side effects like nausea, vomiting, bradycardia (< 50/min), hypotension (>20% of baseline), giddiness and sedation score were recorded.Results:We found the Pethidine group had 62.5% and Dexmedetomidine had 67.5% of grade 3 shivering. The grades of shivering were comparable between the two groups with no statistical difference. We found the dexmedetomidine group had a significant reduction in time required to control shivering and vanishing of shivering after drug.Conclusion:Both dexmedetomidine (0.5mcg/kg) and Pethidine (0.5mg/kg) are effective in treating patients with post-spinal anesthesia shivering but the time taken for control of shivering was shorter with Dexmedetomidine as compared to Pethidine.